Potency of Aloe Vera Extract Transdermal Patch Treatment in Relief Pain and Breast Engorgement - Yustiza, Non Rachmani; Wijayanti, Krisdiana; Sunarjo, Lanny; Widyawati, Melyana Nurul (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Breast engorgement influenced several factors, if not treated properly, can cause mastitis and failure breastfeed. Aloe vera contains flavonoids and tannins, as anti-inflammatories reduce pain and breast engorgement.Purpose : Prove transdermal potency of aloe vera extract patches reducing pain and breast engorgement.Methods: Type of research is quasy experiment, posttest only design with control group. Aloe vera patch as independent variable and dependent variable pain and breast engorgement. There were 32 subjects, divided 2 groups, 16 intervention and 16 controls. The intervention group given aloe vera patches and breastcare, the control group given breastcare. The intervention carried out 2 times a day in morning and evening, pasted 2 hours, 4 consecutive days. The instrument used Six Point Engorgement Scale (SPES) and Numeric Rating Scale (NRS). Data were analyzed using Mann Whitney and Wilcoxon.Results: The reduction breast engorgement scores on fourth day in intervention group had a greater average of 1,57 (p=0,000) than control group, 1,37 (p=0,000). The decrease pain score on fourth day in intervention group had a greater average of 1,44 (p=0,000) than control group 1,31 (p=0,001).Conclusion: The use of aloe vera extract transdermal patches as a non-pharmacological alternative effective reducing pain and breast engorgement.